Pengaruh Pembelajaran Online dan Motivasi Belajar Terhadap Minat Belajar Mahasiswa Akuntansi FEB Universitas Islam Malang - Andreas Apriadana; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The effect of online learning and learning motivation on learning interest of accounting students at FEB Islamic University of Malang need to be identified in order to determine the best way of learning for accounting students when attending online learning. This study aimed to pay attention to the influence of online learning and learning motivation on the learning interest of FEB accounting students at the Islamic University of Malang. The type of research method used is correlational research with a quantitative approach. In this study, the population was all accounting students at the Faculty of Economics and Business, Islamic University of Malang class of 2019. The data source used in this study was Primary Data. In order to take the number of samples in this study using the Slovin formula so that the results obtained for the number of research samples were 68 samples from 213 accounting students class of 2019. Data management was obtained using the SPSS type 26 application. The results obtained in this study can be explained that learning online has a positive effect on learning interest, learning motivation has a positive effect on learning interest.Keywords: Online learning, learning motivation, learning interest